Implementasi Sistem Informasi Perpustakaan Di SDN Sirnajati 01 Berbasis VB.Net - Yoga Religia; Bella Yoviana Hardini (Teknik Informatika, Universitas Pelita Bangsa, 2018)
The development of technological advances in all fields, the use of computers is very helpful, both in the fields of education, trade, industry and health. One sector in the field of education that is currently developing a computerized system is school. School is a formal education to provide knowledge for children. In a school many students need additional lessons or more knowledge, one of them through the library. Research with the title